2019
DOI: 10.1007/s40135-019-00212-1
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulation as a Neuroprotective Strategy for Glaucoma Treatment

Abstract: Purpose of Review This review aims to highlight the current knowledge about inflammatory mechanisms of neurodegeneration in glaucoma with emphasis on potential immunomodulation strategies. Recent Findings Glaucomatous retina and optic nerve present multiple evidences of inflammatory responses of astroglia, microglia, and blood-borne immune cells. Although adaptive/protective responses of resident or systemic immune cells can support neurons and promote tissue repair mechanisms after injurious insults, prolonge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 108 publications
0
23
0
Order By: Relevance
“…A proinflammatory signature acquired by astrocytes upon stress signals may, therefore, lead to tissue destruction and RGC death [ 146 , 147 ]. Along with the capacity to trigger innate immunity signaling pathways, reactive astroglia may also compromise the blood-retina barrier, which further increases the access of systemic immune cells into the retina and the optic nerve [ 137 , 145 ].…”
Section: Dysfunction Of Neuroglial Cellsmentioning
confidence: 99%
See 3 more Smart Citations
“…A proinflammatory signature acquired by astrocytes upon stress signals may, therefore, lead to tissue destruction and RGC death [ 146 , 147 ]. Along with the capacity to trigger innate immunity signaling pathways, reactive astroglia may also compromise the blood-retina barrier, which further increases the access of systemic immune cells into the retina and the optic nerve [ 137 , 145 ].…”
Section: Dysfunction Of Neuroglial Cellsmentioning
confidence: 99%
“…In line with these results, a longitudinal study revealed a gradual increment of serum autoantibodies in glaucoma patients with optic disc hemorrhages and no detectable change in patients with no optic disc hemorrhages [ 217 ]. In addition, the transfer of mononuclear cells from patients with optic disc hemorrhages into immune-deficient mice resulted in increased RGC loss [ 145 , 217 ]. The tracing of circulating monocytes with an inflammatory profile in the DBA/2J model confirmed the entry of these cells into the ONH and its contribution to glaucomatous damage [ 17 ].…”
Section: Activation Of the Immune Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…The microglia and macroglia are involved in inflammatory responses to the injury signal. The proinflammatory cytokines exert an immunostimulatory effect and favor the interaction of glia with T lymphocytes, which are known for their neurodegenerative potential [ 28 , 29 ].…”
Section: Immunomodulationmentioning
confidence: 99%